Ameliorating compaction in a Ghanaian Coastal Savanna Acrisol with compost - Wuaku, Sadata (University of Cape Coast, 2021)
Soil compaction has deletenous effects on crop production by preventing soil to realize its full productive potentials even if crop residue is applied. The study sought to evaluate the efficiency of using compost to ameliorate soil compaction. A research was carried out during the major and minor season of 2019 at the Teaching and Research Farm of the School of Agriculture University of Cape Coast, in the Central Region of Ghana. The experiments were arranged in a randomized complete Block design (RCBD) with four replications. The four different levels of compaction that were imposed were NTP, 3 mild, moderate and high they were used to assess the effect of compaction on the growth of plant. The different types of compost used were maize compost (MC), cassava compost (CC) and pineapple compost (PC). The composts treatments were the sub-plots whilst the main plots were the various forms of soil compaction imposed. Composts were replicated 4 times in each block. In total, there were 48 sub-plots (4 main blocks 3 plots 4 replications). The physical (porosity, bulk density, HC and moisture content) and chemical (pH, CEC, OC, Tot.N and Avai.P) properties of the soil were measured and data collected was subjected to analysis of variance using GenStat Statistical package (12th Edition). Data gathered from the various blocks indicate that regardless of the level of soil compaction, maize compost alleviated soil compaction compared to other composts. In addition, maize compost resulted in the highest grain yield.
xi,121p:,ill.
Keywords: Amelioration; Compaction in soils; Compost; Maize